Designing an innovative, eco-conscious optode for spectrophoto-metric detection of copper across various biological and environmental samples - Abdullah H. Alluhayb; Alaa M. Younis; Alaa S. Amin; Naglaa Mohamed (Talanta Open)
An environmentally sustainable optode has been developed for the detection of copper ions in water-based solutions. The optode was created by immobilizing 2-[6-nitro-2-benzothiazolylazo]-4-hydroxybenzoic acid (NBTHB) onto a porous cellulosic polymer membrane. This immobilization technique is especially beneficial for dye molecules that tend to degrade in alkaline ethylenediamine solutions, which are frequently employed during optode fabrication. The optode demonstrated a linear response to copper(II) ions within the concentration range of 10 to 130 ng mL–1, achieving a high correlation coefficient of 0.9990. The quantification and detection limits were determined to be 10 and 3.0 ng mL–1, respectively. The precision results were reported as % RSD, with intra-day values of 2.30% and 1.65%, and inter-day values of 2.15% and 1.85%, respectively. The selectivity of the sensor membrane was rigorously tested for a various cations and anions, successfully establishing the tolerance limits for interfering species. It could be effectively regenerated by treatment with 0.1 M EDTA, restoring its functionality for repeated use. The optode was effectively employed to measure copper(II) ions in a range of food products, biological fluids, and environmental water samples. The results obtained were comparable to those achieved using the ICP-AES technique, demonstrating the optodes reliability and accuracy.